Auricular acupressure for adverse events following immunization after COVID-19 vaccine injection: A multicentre, blinded, randomized controlled trial. (December 2022) - Fu, Qinwei; Xie, Hui; Zhou, Li; Li, Xinrong; Liu, Yang; Luo, Hongyan; Zhang, Chunyan; Peng, Wenyu; Wang, Zhiqiao; Su, Chang; Xiao, Zhiyong; Lin, Hanwen; et al.
Abstract: Background: Some adverse events following immunization (AEFI) were observed in potential corelation with COVID-19 vaccination but without prevention or ongoing trial for it. We aimed to investigate efficacy of auricular acupressure (AuriAc) therapy in preventing AEFI after first dosage of the vaccine. Methods: We performed a multicentre randomized controlled trial with three arms, including AuriAc, SAuriAc (sham auricular acupressure), and TrAsU (treatment as usual) group, carried out in four medical institutions in Chengdu, China, from March 17th to April 23rd, 2021. We enrolled participants based on eligibility criteria and randomized them into three groups: AuriAc (AEFI-specific auricular points applied, n = 52), SAuriAc (n = 51) or TrAsU (n = 44) group. Primary outcomes were percentages of any AEFI and local pain, and secondary outcomes were percentages who reported other AEFI. They were followed at 1, 3, 5, 7, and 14 days, by phone or online, with severity evaluated. Results: 147 participants (73.47% females) were included with median age as 31 years (25–45, IQR). One day after the injection, participants in AuriAc group reported significant reduction on percentages of any AEFI [intention-to-treat, difference of percentage (DP) = −20.13, 95%CI: − 0.39, − 0.02, p = 0.01; per-protocol, DP = −22.21, 95%CI: − 0.40, − 0.03, P = 0.02] and local pain (per-protocol, DP = −18.40, 95%CI: −0.36, −0.01, P = 0.04), compared with TrAsU group. The effects were slight at other follow-up days and for other outcomes, and with a low percentage of mild local allergic reactions. Conclusions: We firstly explored potential of AuriAc for preventing AEFI related to COVID-19 vaccine injection, which is beneficial for the vaccine recipients, but evidence is limited. Trial registration: chictr.org.cn no. ChiCTR2100043210 (http://www.chictr.org.cn/showproj.aspx?proj=121519 ) Highlights: Neither prevention nor ongoing trial for adverse events following immunization after COVID-19 vaccination. We performed a blinded, three-armed, multicenter randomized controlled trial. We firstly manifested superiority of auricular acupressure for preventing the events. This may also be appropriate for such adverse events of other vaccines.